Can the child penalty be reduced? Evaluating multiple policy interventions - Martin Eckhoff Andresen; Emily Nix (Statistics Norway, Research Department, 2022)
Children cause large earnings drops for mothers but not fathers, a stylized fact known as the "child penalty" that explains a substantial portion of remaining gender income gaps. Can policy reduce the child penalty? We first document how changes in the child penalty over a long time horizon in Norway correlate with major family policy reforms. Next, we evaluate two possible interventions: paternity leave and high-quality childcare. We find no impact of paternity leave on child penalties or a measure of father's preferences for childcare. In contrast, a year of publicly provided childcare reduces child penalties by 23% during the years of use. These results suggest governments can act to reduce child penalties, but providing alternatives to the mother's time, such as quality childcare, is more effective than paternity leave.
Keywords: J21; J23; J22; J71; 330; Gender wage gap; child penalty; paternity leave; childcare